The EFFECT OF CASH HOLDING, PROFITABILITY AND FINANCIAL LEVERAGE ON COMPANY VALUE: Studies on Manufacturing Companies and Basic Industry Sector Chemistry Listed on the IDX for 2018-2020 - wijoyo, fernaldy arie; As'ari, Hasim (PRIMA EKONOMIKA, 2023)
This study aims to determine the effect of cash holding, profitability and financial leverage on firm value, especially in companies in the basic and chemical industrial sectors. This research is a quantitative research with a causal approach. The research operational variables consist of the characteristics of cash holding, profitability and financial leverage as independent variables and firm value as the dependent variable. The research population is Manufacturing Companies in the Basic Industry and Chemical Sector Registered on the IDX in 2018-2020. The sample collection technique was carried out using a purposive sampling technique and the data used were secondary data taken from idx.co.id. Data analysis used the classical assumption test with four steps, namely normality test, heteroscedasticity test, multicollinearity test and autocorrelation test and was processed by multiple linear regression analysis and statistical t test. The results of this study indicate that the three variables have a significant influence on firm value. The results of this study are expected to help companies, especially in the manufacturing sector, maintain cash levels, profits, and pay off debts